Issuance of Business License as a Criminogenic Factor of Environmental Crimes by Corporations - Amrullah, M Arief (Jurnal Cakrawala Hukum, 2024)
Walhi's presentation is related to Ragnhild Sollund's views, which are from the perspective of green critical criminology Environmental damage cannot be seen as simply as depleting forests that are cut down and burned. Companies whose permits have expired leave and neglect mining sites with environmental conditions that become damaged. Excavations form recesses in the middle of which there is a pool of water However, humans and other creatures are also disturbed because their habitats and land are damaged or even extinct because of actions carried out by corporations. Hence, victims are no longer individual but widespread. This article analyses the issuance of permits from authorized officials as an entry point for corporations to exploit natural resources and their contents. To prevent more destructive environmental damage, imposing criminal responsibility on permit-making officials as perpetrators of criminal acts of corruption is necessary so that they are careful and not careless in issuing permits to corporations.How to cite item: Amrullah, M. Arief. â€œIssuance of Business License as a Criminogenic Factor of Environmental Crimes by Corporationsâ€ Jurnal Cakrawala Hukum 15 no. 1 (2024): 14-33. DOI: 10.26905/idjch.v15i1.14365.